lo g 6 ( 3 x + 1 ) = lo g 3 6 ( m x 2 + 3 6 x + 1 )
Let S denote the set of all integers m such that the equation above only has non-negative integer roots (in x ). Find the sum, y ∈ S ∑ ∣ y ∣ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think the fact that it asks for the sum of all possible values of m's absolute value was a little confusing since 6 is counted twice. Although it helps that 50 isn't one of the options.
@Guilherme Dela Corte @Chew-Seong Cheong I think the only accepted values for m are − 6 and − 2 1 . Due to restrictions ( 3 x + 1 > 0 and m x 2 + 3 6 x + 1 > 0 ) all the others values for m are rejected, because either the RHS of the equation has no meaning, or 0 is is a root that is not a positive integer (in the case m = − 1 ). So the answer is wrong and you must edit the problem.
For m = − 1 , the root is x = 3 . I think you might be mistaken.
Log in to reply
In fact, there is a problem with all suggested values of
m
.
For the value
m
=
−
1
, for instance, it is true that the equation has
x
=
3
as a solution, but it is not the only one. The value
x
=
0
is a solution as well and this is not a positive integer, thus the requirement that
the equation has ONLY POSITIVE integer roots
is not satisfied, so the value
m
=
−
1
, as well as all the others, should be excluded. After all, the value
x
=
0
is a trivial root of the original equation, no matter what the value of
m
is.
I guess things can be settled, if you rephrase the first sentence of the problem as follows:
Let m be an integer such that the equation above has only non-negative integer roots.
Finally, there is no reason for the value ∣ m ∣ = 6 to be counted twice. All possible values of ∣ m ∣ are 1 , 3 , 4 , 6 , 7 , 8 and 2 1 , with a sum of 5 0 .
lo g 6 ( 3 x + 1 ) lo g 6 lo g ( 3 x + 1 ) 2 lo g ( 3 x + 1 ) ⟹ ( 3 x + 1 ) 2 9 x 2 + 6 x + 1 ( 9 − m ) x 2 ( 9 − m ) x ⟹ x = lo g 3 6 ( m x 2 + 3 6 x + 1 ) = 2 lo g 6 lo g ( m x 2 + 3 6 x + 1 ) = lo g ( m x 2 + 3 6 x + 1 ) = m x 2 + 3 6 x + 1 = m x 2 + 3 6 x + 1 = 3 0 x = 3 0 = 9 − m 3 0 For x = 0
For x to be a positive integer, 9 − m must be one of the eight positive divisors of 3 0 = 2 ⋅ 3 ⋅ 5 , which are 1 , 2 , 3 , 5 , 6 , 1 0 , 1 5 , 3 0 , when m = 8 , 7 , 6 , 4 , 3 , − 1 , − 6 , − 2 1 and the sum of all ∣ m ∣ is 8 + 7 + 6 + 4 + 3 + 1 + 6 + 2 1 = 5 6 .
Problem Loading...
Note Loading...
Set Loading...
We can rewrite the equation as lo g 6 ( 3 x + 1 ) = 2 lo g 6 ( m x 2 + 3 6 x + 1 ) ↔ 9 x 2 + 6 x + 1 = m x 2 + 3 6 x + 1 ↔ ( 9 − m ) x 2 = 3 0 x → x = 0 or 9 − m 3 0
Because the positive divisors of 3 0 are 1 , 2 , 3 , 5 , 6 , 1 0 , 1 5 , 3 0 , we have that m = − 2 1 , − 6 , − 1 , 3 , 4 , 6 , 7 , 8 .
So our desired answer is 2 1 + 6 + 1 + 3 + 4 + 6 + 7 + 8 = 5 6 .